TikTok Standards and Teen Decadence: A Critical Analysis Based on Jamaluddin Al-Afghani's Thoughts: Tren Standar TikTok dan Dekadensi Sosial Remaja: Analisis Kritis Berdasarkan Pemikiran Jamaluddin Al-Afghani - Khasbiya, Roghdi (Averroes: Journal for Science and Religious Studies, 2025)
Background: This study aims to analyze how TikTok trends influence the social lives of teenagers in Pekalongan Regency and how this phenomenon can be interpreted through Al-Afghani's social perspective, particularly in relation to the role of media and education in shaping social awareness among the community. Method: This study employs a qualitative descriptive research design. Primary data were collected through in-depth interviews with selected TikTok users participating as respondents. Key Findings: This study found that TikTok trends are not merely a form of entertainment but have shaped the social interaction patterns of adolescents. Contribution: The integration of Al-Afghani's perspective to analyze social media phenomena at the local level. This study expands understanding of how symbolic capital and hyperreality are formed among adolescents as a response to global digital trends. Conclusion: TikTok is not merely a trend but creates patterns of symbolic capital and hyperreality, thereby shaping social interaction patterns among adolescents in Pekalongan Regency. This study can be further developed through broader research with a larger sample size or different social media platforms.